2021
DOI: 10.1021/acsomega.1c01604
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Anticancer Evaluation, Enzymatic Assays, and a Molecular Modeling Study of Novel Pyrazole–Indole Hybrids

Abstract: The molecular hybridization concept has recently emerged as a powerful approach in drug discovery. A series of novel indole derivatives linked to the pyrazole moiety were designed and developed via a molecular hybridization protocol as antitumor agents. The target compounds ( 5a – j and 7a – e ) were prepared by the reaction of 5-aminopyrazoles ( 1a – e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 60 publications
0
56
0
Order By: Relevance
“…Furthermore, p53 serves as a transcription factor acting as a tumor suppressor protein. This protein is expressed due to various cellular stresses such as DNA disruption [ 54 ]. It is usually mutated in human cancers [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, p53 serves as a transcription factor acting as a tumor suppressor protein. This protein is expressed due to various cellular stresses such as DNA disruption [ 54 ]. It is usually mutated in human cancers [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various reports revealed that some kinds of caspases are sponsors for starting intracellular event cascade, while others are effectors, producing their effects further downstream resulting in cellular breakdown by intrinsic protein breakdown. Cell shrinkage, chromatin condensation, and DNA fragmentation are all apoptosis events, which need the involvement of caspase-7and caspase-3 [ 48 , 54 , 56 ]. Accordingly, MCF-7 cells were treated with 5 at its IC 50 concentration of 5 μg/mL for 24 h aiming to detect the change in the level of caspase-3and caspase-7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a density of 1 × 10 6 to 3 × 10 6 cells per dish, MCF-7 cells were seeded in 30 mm tissue culture plates in 5 mL of complete medium. 63 More details in the ESI. †…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was carried out according to the manufacturer's protocol. 63 More details in the ESI. †…”
Section: Methodsmentioning
confidence: 99%